The Intuitive Trap: Understanding Cognitive Bias in the Digital Age - Cansu Akoglan (Yeni Medya)
This article presents a philosophical perspective on the relationship between critical thinking and new media, employing dual-process theories to explore the cognitive mechanisms involved. Dual-process theories, which distinguish between fast, intuitive thinking and slower, analytical reasoning, provide a valuable framework for understanding how individuals engage with the overwhelming flow of information in digital environments. The paper argues that while critical thinking is traditionally seen as an analytical activity, more is needed in the context of new media. The fast-paced, heuristic-driven nature of digital content - ranging from rapidly evolving news feeds to algorithm-driven information ecosystems - means that intuitive processes often dominate user engagement, leading to cognitive biases. Therefore, this work advocates for a holistic approach that balances the need for criticality in new media with an understanding of both intuitive and analytical thinking. By offering a novel integration of dual-process theories with media literacy frameworks, this study demonstrates how a comprehensive awareness of cognitive mechanisms can lead to more effective critical engagement with digital content. The findings underscore the importance of a dual approach in fostering both reflective and adaptive new media literacy, and the results highlight the limitations of purely analytical methods while emphasizing the value of heuristic awareness in navigating complex new media environments.